Stolen Childhood and Desolate Future: On Child Marriage in the Makawanpur’s Chepang Community - Budhathoki, Drona (International Research Journal of MMC, 2024)
Child marriage remains a critical issue not only in Nepal but globally, predominantly affecting South Asia, Africa, and Latin America. In Nepal, the Terai region, rural areas, particularly among economically disadvantaged and Dalit communities, faces alarmingly high rates of child marriage. Main objective of this study is to investigate the causes and consequences of child marriage in the Chepang Community. This phenomenon is driven by poverty, social pressure to maintain ties, and the misconception that it offers protection. ADD Primary data has directly been taken from the Chepang community through interview, and Previous studies, book, articles, bulletin, journal are used as a secondary data. This paper employs qualitative research methods, including semi-structured interviews with twenty households and case studies involving two Chepang women, to explore the causes and consequences of child marriage in the study area. Its consequences are profound, directly impacting girls' health and education. Many girls drop out before completing primary education due to domestic responsibilities like cooking and household chores. Early pregnancies, despite physical immaturity, contribute to high maternal and child mortality rates. The statement effectively highlights the multifaceted issue of child marriage in the Chepang community, touching on key factors such as socio-cultural norms, purity, economic pressures, and educational limitations. It also emphasizes the negative impacts of early marriage on health, education, and economic independence, reinforcing cycles of poverty and gender inequality. The proposed solutions education, legal enforcement, awareness, and promoting gender equality are crucial for addressing this issue. However, a deeper exploration of specific interventions tailored to the Chepang community's context could further strengthen the argument.